2019
DOI: 10.1111/jfbc.12935
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antioxidant potential of essential oil and methanol extract from Tunisian and French fennel ( Foeniculum vulgare Mill.) seeds

Abstract: This study was designed to examine the effect of provenance on the phytochemical and antioxidant properties of essential oil and methanolic extract from Tunisian and French fennel seeds (FFS). Analysis of the essential oil showed that although the same main compounds were found in Tunisian and FFS cultivars, some differences were present in their proportions allowing to classify them in two chemotypes. The first class was composed by trans‐anethole (63.41%–78.26%) for Tunisian cultivars and the second one by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 48 publications
4
28
1
Order By: Relevance
“…In addition, there were great differences among the free radical scavenging activities of different extracts and EOs fennel samples, the present result was in agreement with the findings of Ahmed et al., (2019) and Kalleli et al. (2019), suggesting that the free radical scavenging activity of ethanol extracts was superior to that of EOs.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, there were great differences among the free radical scavenging activities of different extracts and EOs fennel samples, the present result was in agreement with the findings of Ahmed et al., (2019) and Kalleli et al. (2019), suggesting that the free radical scavenging activity of ethanol extracts was superior to that of EOs.…”
Section: Discussionsupporting
confidence: 93%
“…Also, research conducted by Kalleli et al. (2019) showed that the yield of EO Tunisian fennel seeds ranged from 3.24% to 5.26%). However, concerning ethanolic extract yields, results are similar to the finding of Oktay et al., (2003) since these authors reported 10.95% yield of ethanolic extracts from conventional fennel seeds.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Due to its broad medical values, L. litseifolius is also called "Guanyin Tea," which means maintaining healthy in Chinese. Similar to other plants, such as kiwifruit and fennel (Kalleli et al, 2019;Saeed et al, 2019), the secondary metabolites and bioactivities of L. litseifolius are significantly affected by the plant genetic variation, geographic location, and cultivars. However, there remain limited studies focusing on the phytochemicals and bioactivities of different L. litseifolius cultivars.…”
mentioning
confidence: 99%